Knowledge management in Colombian higher education: a documentary analysis - Chaparro Prieto, Adriana Yeicy (2024)
Knowledge management is a fundamental process for organizations as it allows maximizing intellectual capital, thus enhancing innovation and improving competitiveness. In higher education institutions, knowledge management is fundamental in promoting academic excellence, even more considering the context variability in which these organizations are immersed. Therefore, the objective of this article is to describe the dynamics of knowledge management in higher education institutions (HEI) in the Colombian context. For this purpose, a documentary review was developed within one specialized database following a qualitative perspective and a hermeneutic approach. To orientate the collection of information, it was stablished an eight (8) years range search algorithm composed of key words. As relevant results, it was evident the importance of research as an articulating element of any knowledge management model in higher education, as well as the added value generated by the dissemination of this asset. Finally, it is discussed the importance of the consolidation of knowledge transfer processes inside higher education institutions to promote the democratization of knowledge with the communities of interest.